The Contribution of Employee Financial Participation to the Governance of the SME in Algeria - Fella Bekhouche Ouahdi; Fatima Zahra Boukhedimi (Financial Markets, Institutions and Risks)
Corporate governance aims to control management decisions and determine their general lines. Thus, the application of the governance system must take into account the nature of the company itself, the conditions in which it operates, its organizational structure and the administrative culture of its actors. While good governance remains the result of good practices. The objective of this article is to demonstrate the contribution of employee financial participation in governance, through the governance regime, the rights to decide and control, the characteristics of employee shareholders in Algeria and thus on performance financial of companies with employee shareholding, based on mechanisms applicable to SME contexts. We will address in a synthetic manner the reality of this contribution of the financial participation of PFS employees through a discussion of the empirical results drawn from a questionnaire survey carried out among employee shareholders working in Algerian SMEs. The results show a low percentage of share capital held by employees with low female participation, an absence of association for employee shareholders, employee shareholding was a financial means to safeguard the activity of public sector companies with critical financial situations. Employee ownership is essential for businesses, promoting employee trust and participation. However, this role is only fully understood by a few companies. It serves as both a collective incentive and a control mechanism. Benefits include better management, financial benefits, business sustainability and job preservation. Despite this, 56.8% of employee shareholders prefer to sell their shares, raising questions about their motivations. A lack of voting rights in the shareholders' council, which requires a review of the regulations to promote employee shareholding in Algeria, in particular for SMEs.